2021
DOI: 10.1080/21655979.2021.1950401
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30b-5p promotes the proliferation and migration of human airway smooth muscle cells induced by platelet-derived growth factor by targeting phosphatase and tensin homolog deleted on chromosome ten

Abstract: Dysfunction of airway smooth muscle (ASM) cells is crucial in asthma pathogenesis. Here, microRNA-30b-5p (miR-30b-5p)’s function and mechanism in ASM cells’ multiplication and migration were investigated. Microarray was utilized for identifying the differentially expressed miRNAs in the bronchial epithelial cells of the asthma patients and healthy controls. Platelet-derived growth factor (PDGF) was employed to treat ASM cells to establish an in-vitro asthma model. Quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Phosphatase and tensin homolog deleted on chromosome ten (PTEN) is a popular oncogene that has been studied in recent years and has a close relationship with tumorigenesis. Recent studies have found that it also plays an important regulatory role in the osteogenic differentiation of MSCs [ 17 , 18 ]. This study focuses on the role of miR-144-3p in MSC proliferation, apoptosis, and osteogenic differentiation under tension and its possible mechanisms.…”
Section: Prefacementioning
confidence: 99%
“…Phosphatase and tensin homolog deleted on chromosome ten (PTEN) is a popular oncogene that has been studied in recent years and has a close relationship with tumorigenesis. Recent studies have found that it also plays an important regulatory role in the osteogenic differentiation of MSCs [ 17 , 18 ]. This study focuses on the role of miR-144-3p in MSC proliferation, apoptosis, and osteogenic differentiation under tension and its possible mechanisms.…”
Section: Prefacementioning
confidence: 99%
“… 35 , 49 Thus, in this study, PDGF‐BB‐induced HASMCs mimic airway remodeling in asthma, and the significant enhancement of HASMC proliferation and migration indicated the success of the model. 36 , 50 In this study, we found that lncRNA ANRIL was upregulated and miR‐7‐5p was downregulated in the serumof patients with asthma and PDGF‐BB‐induced HASMCs. In HASMCs, lncRNA ANRIL negatively regulates miR‐7‐5p.…”
Section: Discussionmentioning
confidence: 57%
“…Among them, PDGF‐BB is widely used to induce ASMC proliferation and migration and aggravate airway remodeling 35,49 . Thus, in this study, PDGF‐BB‐induced HASMCs mimic airway remodeling in asthma, and the significant enhancement of HASMC proliferation and migration indicated the success of the model 36,50 . In this study, we found that lncRNA ANRIL was upregulated and miR‐7‐5p was downregulated in the serumof patients with asthma and PDGF‐BB‐induced HASMCs.…”
Section: Discussionmentioning
confidence: 63%
“…As an inhibitor, miR-590–5p suppressed platelet-derived growth factor (PDGF)-mediated ASMC proliferation via the negative regulation of signal transducer and activator of transcription (STAT) 3 signalling [ 18 ]. In contrast, miR-30b-5p increased in PDGF-stimulated ASMCs and the overexpression of miR-30b-5p facilitated the proliferation and migration of ASMCs by directly targeting phosphatase and tensin homologue (PTEN) and activating the PI3K/Akt pathway [ 19 ]. C hen et al [ 20 ] found an increase in miR-620 in TGF-β1-stimulated ASMCs.…”
Section: Mirnas In Asthmatic Asmcsmentioning
confidence: 99%